La novel·la de la postguerra al País Valencià (1939-1972): entre la problemàtica llengua literària i el desfasament estètic - Simbor, Vicent (Caplletra. Revista Internacional de Filologia, 2015)
This paper is a study about the narrative production between the end of the war and the linguistic standardization in the sixties. It focuses, among other aspects, on the need of the narrative in a context dominated by the poetry, the authors and the novels of the period, the models which define them: realistic pamphlets, religious and social novels and the group of feminine novels.